STRATEGI PEMERINTAH PROVINSI RIAU DALAM MEWUJUDKAN TUJUAN PEMBANGUNAN BERKELANJUTAN UNTUK PENGENTASAN KEMISKINAN - Yustinus Ridarto,; Ridho Afwan, (Proceeding International Conference on Social Sciences, 2026)
This study aims to analyze the strategies of the Riau Provincial Government in achieving the Sustainable Development Goals, particularly Goal 1: No Poverty. Although Riau is endowed with significant natural resources, poverty remains a persistent issue in several districts, especially in rural and coastal areas that experience unequal development. This condition demonstrates the need for a comprehensive, integrated, and sustainable poverty alleviation strategy at the provincial level. The research employs a qualitative descriptive method through the analysis of policy documents, secondary data from the Central Bureau of Statistics (BPS), and relevant literature on SDG implementation at the local government level. The findings indicate that the Riau Provincial Government’s strategy consists of four main components: (1) environmental scanning to identify socio-economic conditions and root causes of poverty; (2) strategy formulation through the integration of poverty reduction programs into the Regional Medium-Term Development Plan (RPJMD) and the Regional Action Plan for SDGs (RAD SDGs); (3) strategy implementation through economic empowerment initiatives, improved access to basic services, and strengthened collaboration among government institutions, private sectors, and community groups; and (4) evaluation and control through monitoring of poverty indicators and program performance. The study reveals several supporting factors, including political commitment, regulatory frameworks, and stakeholder involvement, while inhibiting factors include regional disparities, limited integrated data, and economic dependence on extractive industries. Therefore, this study emphasizes the importance of strengthening governance, enhancing cross-sectoral synergy, and promoting policy innovation to ensure sustainable and inclusive poverty reduction efforts in Riau Province.